Statistical modelling and optimization of hydrolysis of urea to generate ammonia for flue gas conditioning - Mahalik, K.; Sahu, J.N.; Patwardhan, A.V.; Meikap, B.C. (Elsevier, 2010)
The present study is concerned with the technique of producing a relatively small quantity of ammonia which can be used safely in a coal-fired thermal power plant to improve the efficiency of electrostatic precipitator by removing the suspended particulate material mostly fly ash, from the flue gas. In this work hydrolysis of urea has been conducted in a batch reactor at atmospheric pressure to study the different reaction variables such as reaction temperature, initial concentration and stirring speed on the conversion by using design expert software. A 2(3) full factorial central composite design (CCD) has been employed and a quadratic model equation has been developed. The study reveals that conversion increases exponentially with an increase in temperature, stirring speed and feed concentration. However the stirring speed has the greatest effect on the conversion with concentration and temperature exerting least and moderate effect respectively. The values of equilibrium conversion obtained through the developed models are found to agree well with their corresponding experimental counterparts with a satisfactory correlation coefficient of 93%. The developed quadratic model was optimized using quadratic programming to maximize conversion of urea within experimental range studied. The optimum production condition has been found to be at the temperature of 130 degrees C, feed concentration of 4.16 mol/l and stirring speed of 400 rpm and the corresponding conversion, 63.242%. (C) 2010 Elsevier B.V. All rights reserved.